2019
DOI: 10.1007/s11442-019-1995-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the regional climate variations on lake changes of Zabuye, Dangqiong Co and Bankog Co salt lakes in Tibet

Abstract: The lake hydrological and meteorological data of the Tibetan Plateau are not rich. This research reports the observed climatic data and measured water levels of saline lakes from the local meteorological stations in the Zabuye salt lake, the Dangqiong Co salt lake and the Bankog Co salt lake in recent two decades. Combining with satellite remote sensing maps, we have analyzed the changes of the water level of these three lakes in recent years and discussed the origins of the changes induced by the meteorologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The rainfall in the rainy season is mostly in the form of short-term thunderstorms. As can be seen from Figure 8, the water level of the North Lake of the Zabuye Lake shows an upward trend, corresponding to the trend of climate change (Wang et al, 2019). During the period from 1991 to 2020, the lowest annual average water level was 4,420.79 m in 1997, and the highest annual average water level was 4,421.61 m in 2020.…”
Section: Regional Climate Changementioning
confidence: 88%
See 1 more Smart Citation
“…The rainfall in the rainy season is mostly in the form of short-term thunderstorms. As can be seen from Figure 8, the water level of the North Lake of the Zabuye Lake shows an upward trend, corresponding to the trend of climate change (Wang et al, 2019). During the period from 1991 to 2020, the lowest annual average water level was 4,420.79 m in 1997, and the highest annual average water level was 4,421.61 m in 2020.…”
Section: Regional Climate Changementioning
confidence: 88%
“…Single-factor evaporation experiments revealed that an increase in precipitation and a decrease in annual lake evaporation over the past 30 years have resulted in an 18% increase in the total lake area. Wang et al (2019) analyzed single-factor climate variables with the aid of the observational data from Zabuye Salt Lake and Dangxiongcuo Salt Lake in Tibet, and found that the lake water level increased by 0.032 m/yr from 2004 to 2014. It was believed that the main reason for the rise of lake water level was the effects of changes in seasonal climate and water supply type.…”
Section: Introductionmentioning
confidence: 99%